2021
DOI: 10.3390/jor1020014
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Thoracocentesis and Chest Drain Insertion: A Single Centre Study from the North East of England

Abstract: Introduction: There are no prospective studies looking at complications of pleural procedures. Previous British Thoracic Society Pleural audits and retrospective case series inform current practice. Incidence of any complication is between 1–15%. We sought to add to the existing literature and inform local practice with regards to intercostal drains and thoracocenteses. Methods: Local Caldicott approval was sought for a review of all inpatient adult pleural procedures coded as ‘T122 drainage of pleural cavity’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…A previous study suggested that pleural pressure decreases significantly with removing a large volume of pleural fluid; visceral pleura may rupture and cause a pneumothorax (Shimoda et al, 2021). In the current study, bilateral procedures increased the risk of pneumothorax, unlike a previous study, which did not report any association between bilateral function and pneumothorax (Jackson et al, 2021).…”
Section: Discussioncontrasting
confidence: 83%
“…A previous study suggested that pleural pressure decreases significantly with removing a large volume of pleural fluid; visceral pleura may rupture and cause a pneumothorax (Shimoda et al, 2021). In the current study, bilateral procedures increased the risk of pneumothorax, unlike a previous study, which did not report any association between bilateral function and pneumothorax (Jackson et al, 2021).…”
Section: Discussioncontrasting
confidence: 83%
“…In countries with a high prevalence of TB, a ruptured cavity of TB can be a cause of pneumothorax or hydropneumothorax. Hydropneumothorax can be diagnosed according to pleural fluid analysis, pleural fluid culture, CXR, or thorax CT scan [33] . Thorax CT scan is important for etiological diagnosis because it is easier and faster than pleural fluid analysis, therefore it can be used as an initial examination.…”
Section: Discussionmentioning
confidence: 99%
“…An intercostal drain (ICD) device is inserted for drainage. In cases with TB etiology, ICD insertion may take longer, up to 30 days [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of complication rates is limited because of a lack of prior studies reporting pleural procedure complication rates. Only one British single‐centre study, by Jackson et al ., 15 reported the majority of complications contained in the BTS audits, with an 8% overall complication rate. Future audits should aim to report the same complications to allow for direct comparisons.…”
Section: Discussionmentioning
confidence: 99%